Coloring mixed hypergraphs: from combinatorics to philosophy - Vitaly Voloshin (Le Matematiche, 2004)
We survey recent results and open problems on the chromatic spectrum, planarity and colorability of mixed hypergraphs and their relations to such categories of philosophy as identity and difference.